Patterns of Islamic Banks Financing to Increase the Number of Halal Tourism and the Local Generated Income (PAD) Growth In Indonesia - Fadli Muhammad (Universitas Muhammadiyah Malang, 2019)
This study aims to analyze the relationship of Islamic bank financing to the increase the number of halal tourists and the growth the local generated income (PAD) period 2015-2016 in 33 provinces, Indonesia. Using the research method is granger causality and panel data multiple regression with the Minitab analytical tool. This model analyzes the influence of Islamic bank financing contributions to the number of halal tours and the local generated income. The amount of Islamic banks financing in the tourism sector such as restaurant and tourism business has contributed to increase the number of halal tourists and the growth of the local generated income (PAD). The results of this study can be used for the Islamic banking industry to support capital financing for the halal industry. In previous studies only analyzed the halal tourism potential, as well as the potential of the tourism industry in general for the local generated income. However, this study discusses the contribution of Islamic bank financing to the number of halal tourism and an increase in the local generated income.